Weighted log-normal kernel density estimation. Issue 22 (16th November 2016) - Igarashi, Gaku
ABSTRACT: The log-normal (LN) kernel estimator of a density with support [0, ∞) was discussed by Jin and Kawczak (2003 ). The contribution of this paper is to suggest a new class of LN kernel estimators using the idea of weighted distribution. The asymptotic properties of the new class of estimators are studied. Also, numerical studies based on both simulated and real data set are presented.